IDEAL Stage 2a experience with in-office, transperineal MRI/ultrasound software fusion targeted prostate biopsy. Issue 1 (21st November 2019) - Tzeng, Michael; Cricco-Lizza, Eliza; Al Hussein Al Awamlh, Bashir; Pantuck, Morgan; Margolis, Daniel J; Yu, Miko; Hu, Jim
Abstract : Objective: Although the feasibility of transperineal biopsy under local anesthesia has been demonstrated, little is known regarding the application of MRI/ultrasound software fusion targeted biopsy for transperineal biopsy under local anesthesia. The objective of our study is to describe our initial experience with in-office transperineal MRI/ultrasound software fusion targeted biopsy (Idea, Development, Exploration, Assessment, Long-term Follow-up [IDEAL] Stage 2a). Methods: Between October 2017 and July 2019, 33 men underwent in-office transperineal MRI-targeted biopsy using the Artemis (Eigen, Grass Valley, CA, USA) fixed-robotic arm system. The indication for biopsy was elevated prostate specific antigen (PSA) (n=14), prior negative biopsy (n=10), active surveillance (n=6), and surveillance after partial gland cryoablation (n=3). We prospectively captured patient demographic and clinical characteristics, biopsy outcomes, and complications. Complications were classified according to Common Terminology Criteria for Adverse Events (CTCAE) V.5.0. Results: The median patient age was 67 years (IQR 61–71) and the median serum PSA level was 7.0 ng/mL (IQR 5.1–11.4). The median duration of in-office MRI-targeted transperineal biopsy was 26 min (IQR 23–28). Overall, transperineal MRI-targeted biopsy detected prostate cancer in 18 (54.6%) men, with 8 (24.2%) being clinically significant (Gleason Score ≥3+4, Grade Group ≥2). Clinically significant prostate cancer was detected in four (28.6%) biopsy naïve men, two (20.0%) men with a prior negative, one (16.7%) man on active surveillance and one (33.3%) man following partial gland ablation. Three (9.1%) men experienced complications: two hematuria and one urinary retention. Conclusion: Our findings demonstrate the feasibility of the fixed-robotic arm fusion platform for in-office transperineal MRI-targeted biopsy and a low rate of adverse events. However, larger prostate size precludes MRI/ultrasound software fusion and pubic arch interference hindered the transperineal MRI-targeted approach in 9.1% of men. Pubic arch interference was overcome by a free-hand approach with software fusion guidance.